Keselamatan Sebagai Pembebasan Batin dan Penenbusan Ilahi: Analisis Komparatif Sapta Darma dan Teologi Reformed - Widyawati Sultana; Jonathan Octavianus (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2026)
This study is based on the reality that the understanding of salvation within religious societies is not singular, particularly in the pluralistic context of Indonesia. Sapta Darma, as one of the indigenous belief systems, views salvation as inner liberation achieved through spiritual exercises and a harmonious way of life, whereas Reformed theology understands salvation as the work of God in saving humanity from sin through Jesus Christ. This study aims to examine the concept of salvation in Sapta Darma, compare it with Reformed theology, and evaluate its theological implications. The method used is a qualitative approach through library research with descriptive, analytical, and comparative characteristics. The findings show that Sapta Darma emphasizes salvation as a subjective process of self-cultivation centered on inner experience, while Reformed theology emphasizes salvation as an objective act of God rooted in the redemptive work of Christ. This study concludes that the two concepts cannot be equated because they arise from fundamentally different foundations of thought. The novelty of this research lies in its comparative analysis of the concept of salvation in Sapta Darma from the perspective of Reformed theology.